4(3w+1)+4v=4(v-6)-2v

Simple and best practice solution for 4(3w+1)+4v=4(v-6)-2v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3w+1)+4v=4(v-6)-2v equation:


Simplifying
4(3w + 1) + 4v = 4(v + -6) + -2v

Reorder the terms:
4(1 + 3w) + 4v = 4(v + -6) + -2v
(1 * 4 + 3w * 4) + 4v = 4(v + -6) + -2v
(4 + 12w) + 4v = 4(v + -6) + -2v

Reorder the terms:
4 + 4v + 12w = 4(v + -6) + -2v

Reorder the terms:
4 + 4v + 12w = 4(-6 + v) + -2v
4 + 4v + 12w = (-6 * 4 + v * 4) + -2v
4 + 4v + 12w = (-24 + 4v) + -2v

Combine like terms: 4v + -2v = 2v
4 + 4v + 12w = -24 + 2v

Solving
4 + 4v + 12w = -24 + 2v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-2v' to each side of the equation.
4 + 4v + -2v + 12w = -24 + 2v + -2v

Combine like terms: 4v + -2v = 2v
4 + 2v + 12w = -24 + 2v + -2v

Combine like terms: 2v + -2v = 0
4 + 2v + 12w = -24 + 0
4 + 2v + 12w = -24

Add '-4' to each side of the equation.
4 + 2v + -4 + 12w = -24 + -4

Reorder the terms:
4 + -4 + 2v + 12w = -24 + -4

Combine like terms: 4 + -4 = 0
0 + 2v + 12w = -24 + -4
2v + 12w = -24 + -4

Combine like terms: -24 + -4 = -28
2v + 12w = -28

Add '-12w' to each side of the equation.
2v + 12w + -12w = -28 + -12w

Combine like terms: 12w + -12w = 0
2v + 0 = -28 + -12w
2v = -28 + -12w

Divide each side by '2'.
v = -14 + -6w

Simplifying
v = -14 + -6w

See similar equations:

| 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= | | 4x=28-0.25(4-16x) | | 5n-6(n+2)=14 | | -8(3x-4)+1=15 | | 5s+3s=56 | | (2x+6a)-(4x-a)= | | 8x=14-0.5(10x+2) | | 2z=-10 |

Equations solver categories